Root coverage assessment: validity and reproducibility of an image analysis system - Ste´phane Kerner (Blackwell Synergy, 2007)
Aim: The aim of this methodological study was to validate a new method for root coverage evaluation following periodontal plastic surgery. Material and Methods: Thirty recessions were treated in 21 consecutive patients, using a subepithelial connective tissue graft technique. Clinical measurements and photographs were taken at baseline and 12 6 months after treatment. The mean percentage of root coverage for linear and surface area measurements was calculated using conventional clinical evaluation, and compared with ImageJ, a public domain Java image processing program. Bland–Altman plots were used for assessing repeatability and agreement between clinical and ImageJ measurements. The strength of the relationship was calculated using the Pearson product moment correlation coefficient. Results: The repeatability of ImageJ was excellent for both linear and surface area measurements. The agreement between clinical and ImageJ measurements was good for the linear evaluation, showing lower and upper limits of 13.14% and 17.42%, respectively. Significant correlations (po0.001) were found between clinical and ImageJ measurements, ranging from 0.93 to 0.94 for linear evaluation, and from 0.89 to 0.90 for surface evaluation. Conclusions: The outcomes of this study show that the ImageJ analysis is a reliable, reproducible method to evaluate the percentage of root coverage after periodontal plastic surgery, when a midfacial linear measurement is used.